Green synthesis of silver nanoparticles using Ocimum sanctum for efficient Congo red dye removal: a response surface methodology approach - S. Murugeshwari; B. Senthil Rathi; N. Kalaiarasi; R. M. Saravana Kumar; I. Arunkumar; M. Vasanth; P. Senthil Kumar; Gayathri Rangasamy (Environmental Monitoring and Assessment, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

The genetic architecture of tristyly and its breakdown to self‐fertilization - Ramesh Arunkumar; Wei Wang; Stephen I. Wright; Spencer C. H. Barrett (Molecular Ecology, 2017)
The floral polymorphism tristyly involves three style morphs with a reciprocal arrangement of stigma and anther heights governed by two diallelic loci ( S and M ). Tristyly functions to promote cross‐pollination, but modifications to stamen position commonly cause transitions to selfing. Here, we integrate whole‐genome sequencing and genetic mapping to investigate the genetic architecture of the M locus and the genetic basis of independent transitions to selfing in tristylous Eichhornia paniculata . We crossed independently derived semi‐homostylous selfing variants of the long‐ and mid‐styled morph fixed for alternate alleles at the M locus ( ssmm and ssMM , respectively), and backcrossed the F 1 to the parental ssmm genotype. We phenotyped and genotyped 462 backcross progeny using 1450 genotyping‐by‐sequencing (GBS) markers and performed composite interval mapping to identify quantitative trait loci (QTL) governing style‐length and anther‐height variation. A QTL associated with the primary style‐morph differences (style length and anther height) mapped to linkage group 5 and spanned ~13–27.5 Mbp of assembled sequence. Bulk segregant analysis identified 334 genes containing SNPs potentially linked to the M locus. The stamen modifications characterizing each selfing variant were governed by loci on different linkage groups. Our results provide an important step towards identifying the M locus and demonstrate that transitions to selfing have originated by independent sets of mating‐system modifier genes unlinked to the M locus, a pattern inconsistent with a recombinational origin of selfing variants at a putative supergene.